The Benefits of Moringa Oleifera to Prevent Stunting Diseases in Mugarsari District, Tasikmalaya - Nuryati, Rina; Priyadi, Rudi; Juhaeni, Ade Hilman; Faqihudin, Faqihudin; Bunda, Cici Aulia Permata; Azhari, Septian Cahya (Jurnal Pengabdian Pancasila (JPP), 2024)
Stunting is a serious health problem in Indonesia, especially in rural areas such as Mugarsari Sub-district, Tasikmalaya. This condition is caused by a lack of adequate nutritional intake during a child's growth period, which can result in impaired physical and cognitive development. This community service aims to increase community awareness and knowledge about the benefits of Moringa oleifera, or Moringa leaves, in stunting prevention. Community service activities include education, training, and mentoring to the community regarding the planting, processing, and consumption of Moringa oleifera as a critical source of nutrition. The results of this program show an increase in community awareness about the importance of balanced nutrition and the potential of Moringa oleifera as a natural solution in overcoming stunting. In addition, the programme also succeeded in encouraging the community to independently utilise Moringa oleifera in their daily diet, which in turn is expected to reduce the stunting rate in this region.